2000
DOI: 10.1073/pnas.97.2.593
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a linear search in bimolecular 3′ splice site AG selection

Abstract: In most eukaryotic introns the 3 splice site is defined by a surprisingly short AG consensus found a variable distance downstream of the branch site. Exactly how the spliceosome determines which AG to use, however, is not well understood. Previously we showed that when the branch site and 3 splice site AG are supplied by separate RNA molecules, there is a strong preference for use of the 5 -most AG in the 3 splice site-containing RNA. Here we show that this apparent 5 33 directionality holds even when this RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 33 publications
7
43
0
Order By: Relevance
“…In introns with distant BPs (dBPs) and PPTs, the 39 ss is located by a scanning process from the BP to the first downstream AG (Smith et al , 1993Liu et al 1997). Similar scanning behavior is observed in bimolecular exon ligation experiments (Chen et al 2000). Consequently, one prerequisite of the region between distant BPs and the 39 ss is that it lacks any other AG dinucleotides leading to its designation as the AG-exclusion zone (AGEZ) (Gooding et al 2006).…”
Section: Introductionmentioning
confidence: 50%
“…In introns with distant BPs (dBPs) and PPTs, the 39 ss is located by a scanning process from the BP to the first downstream AG (Smith et al , 1993Liu et al 1997). Similar scanning behavior is observed in bimolecular exon ligation experiments (Chen et al 2000). Consequently, one prerequisite of the region between distant BPs and the 39 ss is that it lacks any other AG dinucleotides leading to its designation as the AG-exclusion zone (AGEZ) (Gooding et al 2006).…”
Section: Introductionmentioning
confidence: 50%
“…According to the scanning model, identification of the correct 3ЈSS AG occurs by a linear search mechanism, assuming that the spliceosome begins scanning at the branch point and selects the first downstream AG dinucleotide (39). This model is supported by research with HeLa cells, in which splicing is blocked when hairpin loops are inserted upstream of the AG splice site, possibly preventing movement of the spliceosome (3). With a bimolecular exon ligation assay, it was also shown that the substrate with the 5Ј-most AG is selected among different 3Ј RNA substrates and that no poly(Y) tract was necessary for the second catalytic step (1,3).…”
mentioning
confidence: 89%
“…The shift in splice site usage (confirmed by cDNA sequencing) adds two additional amino acids to the exon. This IGHD3 ␦6 splice site reflects the introduction of an AG dinucleotide and the preferential use of the more 5Ј AG as a splice acceptor site (31,32). In toto there are 24 insertions/deletions between these two ␦ genes, with most being short, i.e., 14 are Ͻ5 bp.…”
Section: Catfish and ␦ Genesmentioning
confidence: 99%